El proceso de creación de la Organización Mundial de la Salud y la Guerra Fría - Cueto, Marcos (2011)
This article studies the political and medical processes in which the World Health Organization emerged and was formally created in 1948 as the main multilateral agency in health linked to the recently created United Nations. These processes begun in 1945 when the United States and the Soviet Union began to work together to defeat the Nazis and ended shortly after the beginning of the Cold War in 1947, namely after the rivalry and competition between Soviet and North-American superpowers that would take place during the second half of the 20th century. The World Health Organization could validate itself in a changing context and left a legacy that today is relevant for contemporary public health.